Fatigue in sport and exercise - Phillips, S. (Routledge, 2024)
Fatigue is an important concern for athletes at all levels, recreational sport and exercise participants, athletic coaches, personal trainers, and fitness professionals. The study of fatigue is also important for students of the sport, exercise, and health sciences, as it enables a deeper understanding of fundamental physical function and the limitations behind human performance.